1985
DOI: 10.1115/1.3247513
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Periodic Natural Convection in a Rectangular Enclosure of Aspect Ratio One

Abstract: A two-dimensional rectangular cavity of aspect ratio one is studied experimentally using a laser-doppler velocimeter. The enclosure is air filled and consists of two vertical walls at unequal isothermal temperatures and two connecting horizontal walls with temperatures varying linearly between the two vertical surfaces. This study clearly defines the existence of periodic laminar flow regimes detectable at Ra numbers above 0.3 × 107. These periodic variations in velocity are induced by the upper and lower boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
6
25
0
1
Order By: Relevance
“…Using a time-dependent finite-difference code, these authors found that the onset of oscillations occurs at a Rayleigh number between 2 × 10 6 and 2.2 × 10 6 . Parallel to this, in an experimental study of a square cavity with conducting horizontal walls, Briggs and Jones [18] found a transition from steady to oscillatory flow behavior at a Rayleigh number of 3 × 10 6 . It was proclaimed in this work that the regime of periodic convective flows persisted to a Rayleigh number of at least 1.2 × 10 7 .…”
Section: Numerical Computationsmentioning
confidence: 92%
“…Using a time-dependent finite-difference code, these authors found that the onset of oscillations occurs at a Rayleigh number between 2 × 10 6 and 2.2 × 10 6 . Parallel to this, in an experimental study of a square cavity with conducting horizontal walls, Briggs and Jones [18] found a transition from steady to oscillatory flow behavior at a Rayleigh number of 3 × 10 6 . It was proclaimed in this work that the regime of periodic convective flows persisted to a Rayleigh number of at least 1.2 × 10 7 .…”
Section: Numerical Computationsmentioning
confidence: 92%
“…Let us quote also those of Briggs et al [10] and Penot et al [11] both dealing with the thermal exchanges occurring in parallelepipedic cavities with two active vertical walls, the rest being adiabatic. The study in [10] is in particular devoted to the analysis of the multicellular flows which take place in these cavities.…”
Section: Introductionmentioning
confidence: 98%
“…The study in [10] is in particular devoted to the analysis of the multicellular flows which take place in these cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Yet all convective flows become turbulent at sufficiently high Rayleigh number, and many are oscillatory over a range of Rayleigh numbers which usually lies between the laminar and turbulent regimes. This question of the reality of the steady solutions was addressed recently by Briggs and Jones (1985) in an experimental study of the double-glazing problem with conducting horizontal surfaces. They found a transition from steady to oscillatory free convection in a square, air-filled cavity at a Rayleigh number of 3 x 10 s with a simple periodicity of about 0.5 Hz at onset.…”
Section: Introductionmentioning
confidence: 98%